Considerations on Standardization in Smart Hospitals - Sun-Ju Ahn; Sungin Lee; Chi Hye Park; Da Yeon Kwon; Sooyeon Jeon; Han Byeol Lee; Sang Rok Oh (한국보건행정학회, 2024)
Smart hospitals involve the use of recent ICT (information and communications technology) technologies to improve healthcare access,efficiency, and effectiveness. Standardization in smart hospital technologies is crucial for interoperability, scalability, policy formulation, qualitycontrol, and maintenance. This study reviewed relevant international standards for smart hospitals and the organizations that develop them. Specific attention was paid to robotics in smart hospitals and the potential for standardization in this area. The study used online resources andexisting standards to analyze technologies, standards, and practices in smart hospitals. Key technologies of smart hospitals were identified. Relevant standards from ISO (International Organization for Standardization) and IEC (International Electrotechnical Commission) were mappedto each core technology. Korea’s leadership in smart hospital technology were highlighted. Approaches for standardizing smart hospitals wereproposed. Finally, potential new international standard items for robotics in smart hospitals were identified and categorized by function:sampling, remote operation, delivery, disinfection, and movement tracking/contact tracing. Standardization in smart hospital technologies iscrucial for ensuring interoperability, scalability, ethical use of artificial intelligence, and quality control. Implementing international standards insmart hospitals is expected to benefit individuals, healthcare institutions, nations, and industry by improving healthcare access, quality, andcompetitiveness.